A public and a private university in one: Equity in university attendance in Kenya since the liberalization reforms of the 1990s - Rebecca Simson; J. Andrew Harris (United Nations Research Institute for Social Development (UNRISD), 2020)
Until the 1990s Kenya had a selective state-financed university system where students bore few educational costs. This limited the number of university students that the government could afford to educate and created fierce competition for university places. In the late 1990s the Kenyan government responded to this crisis in supply by liberalizing the tertiary sector. Barriers to accreditation of private universities were loosened and public universities began to establish parallel, fee-paying programmes, which only required applicants to meet minimum entry requirements, alongside the state-sponsored, selective programmes. By the late 2000s self-financed students accounted for roughly half of university admissions. Consequently, undergraduate enrolment rose sharply, from 33,000 in 1999, to close to 500,000 by 2017. The number of universities increased from a single public university in Nairobi in 1970, to over 50 tertiary institutions nationwide by 2014. [...] We find that horizontal inequalities in university access - between ethnic and religious groups and the sexes - have declined, while vertical, "class", inequality is likely increasing. Using a subsample of University of Nairobi graduates, we argue that parallel degree programmes absorbed a higher share of women and ethnic minorities than through the regular competitive admission stream, but that these students were on average from higher socioeconomic backgrounds. In this sense, the programmes are regressive. However, this should not overshadow the fact that students entering through the regular, meritocratic track are on average from socioeconomically privileged backgrounds too. We also show that intergenerational persistence in university access in Kenya is considerable, and its high level predates the reforms of the 1990s.
Keywords: 330; Higher education; universities; inequality; Kenya